ASSESSMENT OF SELECTED BODY COMPOSITION VARIABLES AMONG THROWERS AND JUMPERS OF PUNJABI UNIVERSITY PATIALA - Raj Kumar; Kulwinder Mani; Mehul Puri (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2024)
The purpose of present study was to compare the body fat, protein, salt, to various department of Punjabi university Patiala. For this study, total 20 male’s subjects (10 thrower ,10 jumpers) belong to 18 to 25 years of age were taken. The study was conducted on males of Punjabi university Patiala. All the samples were taken by applying purposive sample technique. The level of significance was set at 0.05. The body composition variables chosen was body fat, protein, salt. Comparative statistics were used to analyses the results, which conclusively showed significance difference between thrower and jumpers. The t -value of body fat is (2.4417), the t value of protein is (1.9664), the t value of salt (1.1177) at 0.05 level and degree of freedom is set at 18. So, it is demonstrated that there is a significant difference between the thrower and jumper players for their body fat.